REDUKSI LOGAM BERAT CHROMIUM (VI) DENGAN FOTOKATALIS KOMPOSIT TiO2-SiO2 - Candra Purnawan (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractsComposite TiO2-SiO2 has been synthesized using sol-gel process with starting materialsTiCl4 and Na2SiO3. The purposes of this research were to know the effect of compositecomposition, pH solution and UV radiation time for reduced Chromium (VI) cations. Theidentification and characterization of composite were done by infrared spectroscopy (IR)and X-Ray Diffraction. Condition of Chromium (VI) reduction by composite TiO2-SiO2 werecarried out with variation of composite TiO2-SiO2 concentration or the ratio Ti:Si were1:0,1 ; 1:0,5 ; 1:1 ; 1:1,5 ; 1:2. Variation of pH solution in 3,0; 3,5; 4,0; 4,5; 5,0; 5,5; 6,0; 6,5;7,0 and variation of UV radiation times in 2, 4, 6, 12, 18, 24, 30, 36, 42, 48 hours.The result showed that XRD characteristic of TiO2-SiO2 composite showed 2q peaks at 22.94degrees and 36.24 degrees. IR characteristic of TiO2-SiO2 showed absorption of Ti-O-Si inthe wave number 962 cm-1. The optimum reduction of Chromium (VI) cations using TiO2-SiO2 composite in Ti:Si = 1:1 composition, pH 3 and with 18 hours radiation times.